Critical Pathways to Disability Decarceration: Reading Liat Ben-Moshe and Linda Steele - Wildeman, Sheila (feminists@law, 2023)
I consider how Liat Ben-Moshe’s Decarcerating Disability and Linda Steele’s Disability, Criminal Justice and Law: Reconsidering Court Diversion contribute to emerging conversations between critical disability studies and anti-carceral studies, and between disability deinstitutionalization and prison abolitionism. I ask: what if any role might law, or specifically rights-based litigation, play in resisting carceral state strategies and redirecting material and conceptual resources toward supports for diverse forms of flourishing? I centre my remarks on the special relevance of Ben-Moshe’s and Steele’s books to social movement activism in Atlantic Canada and critical reappraisal of Canada’s solitary confinement litigation.